Chaos in the pulse spacing of passive Q-switched all-solid-state lasers - Kovalsky, Marcelo Gregorio (2010)
We report the experimental and theoretical verification that, in a diode-pumped Nd:YAG + Cr:YAG Q-switched laser, the instabilities in the pulse spacing ("jitter") are ruled by low-dimensional deterministic chaos. From our experimental time series, we determine the embedding and fractal dimensions of the attractor, as well as the values of the Lyapunov exponents. We also present a simplified theoretical description in terms of a map of the same universality class as the logistic map, which explains the bifurcations' cascade and the period-three window of stability observed. The achieved characterization of the dynamics and its main parameters opens a door to effective ways to reduce the jitter, which is of practical interest, through mechanisms of control of chaos. Conversely, the difficulty in the prediction of the interpulse spacing makes this system attractive for high power, robust FM chaotic laser cryptography in free-space propagation.